Identification of Relative Age and Depositional Environment of Gumai Formation Based on Characteristics of Planktonic and Benthonic Foraminifera in Carbonaceous Sandstone, Keban Agung Area, Lahat Regency, South Sumatra Province - Yusar, Adri Taufiqurrahman; Idarwati, Idarwati (Universitas Negeri Gorontalo, 2025)
The administrative location of the study area is in Keban Agung area, Lahat Regency, South Sumatra Province. This study aims to determine the age and depositional environment of the Gumai Formation of the study area based on the characteristics of planktonic and benthonic Foraminifera found. The abundant distribution of Carbonatan sandstone is an attraction to determine the depositional environment of the study area. The methods used in this research are literature study, field observation, micropaleontological analysis with relative age inference and micropaleontological analysis with P/B ratio calculation. Planktonic foraminifera fossils found in the study area are Orbulina universa, Globigerina praebulloides, Globigerina seminulina, Catapsydrax dissimilis, and Globigerinoides obliquus and benthonic foraminifera fossils found in the study area are Tubinella Inornata, Astrononion stelligerum, Hoglundina elegans, Quinqueloculina lamarckiana and Cibicides robertsonianus, then obtained the age and environment of deposition of the Gumai Formation in the study area based on the method of drawing relative age (Blow, 1969) and the P / B ratio, namely Early Miocene - Middle Miocene and Neritic Edge - Middle Neritic.